Multivariate analysis on lettuce performance in response to irrigation blades and water salinity levels in two growing environments (Research, Society and Development, 2020)
The objective was to analyze the growth and yield of lettuce under the effect of the interaction of the blade and of water salinity in both cultivation environments. The experiment was conducted in the field and protected environment at UFAL. The experimental design for both environments was in randomized blocks, with a 5x5 factorial scheme, with 5 replications, with 25 treatments and 125 experimental units. The treatments consisted of the interaction of 5 irrigation depths and 5 water salinity levels. Were analyzed and processed 18 variables and using the statistical software R. The results showed that the principal component analysis apresented blades with 100 and 75% ETc being the best in both environments. Salinity had greater variation in the field and the blade in the protected. The water salinity level S4 (in both environments) directly interfered in the performance of the 18 variables. The main component analysis had better performance of the variables in the interaction L3S3 for the field and L1S1 for protected. In the field, the interactions L1S4 and L1S5 obtained less similarities and L4S2 and L5S5 the greater, occurring the opposite in the protected with dissimilarity between L2S1 and L3S3 and similarity between L2S1 and L2S3. The Cluster hierarchical analysis showed that MFF and DC are the most important variables among the others. For both environments, lettuce responded better with the highest blades and lowest levels salinities for biometric variables followed by the productivity variables and the lowest blades and salinity below the culture threshold for the chlorophyll index.